Modeling of a Road Traffic Accident Using Multivariate Analysis of Injuries in a Two-Wheeled Vehicle Collision with a Car - Evtyukov, S. A.; Brylev, I. S.; Blinder, M. M.; Rogov, V. R.; Ptitsyn, D. A. (2021 Systems of Signals Generating and Processing in the Field of on Board Communications, 2021)
The purpose of this study is to study the kinematics of the road accidents movement and the factors influencing the degree of injury from collisions of a two-wheeled vehicle with a car by modeling a road traffic accident. The analysis of the effect of vehicle speed on the degree of injury for a certain moment of collision has been carried out. A quantitative assessment is given to the factors influencing the degree of injury from road accidents. Depending on the vehicle speed, collision time, graphs were built and regression equations were obtained.